2013
DOI: 10.2174/1874325001307010600
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Component Anteversion in Primary and Revision Total Hip Arthroplasty: An Observational Study

Abstract: Purpose: In a prospective manner to evaluate the range of acetabular component anteversion actually achieved by the use of a cup positioner in cementless revision and primary THA.Methods: We operated 71 patients with cementless primary THA, and 26 patients with cementless acetabular revision surgery. We aimed to obtain cup anteversion of 10 to 30° with an impactor-positioner. In all cases we used elevated liners and a ceramic head with diameter 28. At 3 months postoperatively the component versions were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, there still exists a dearth of literature regarding the effects of acetabular component positioning on hip functional outcome scores and till date patient satisfaction as a primary outcome in relation to acetabular version has not been done. Reikeras et al [12] concluded that cross-table radiography provides acceptable information for clinical use. Reikeras et al [13] studied that the range of acetabular component anteversion actually achieved by the use of a cup positioner by the freehand technique in many cases was not within the intended range of 10 to 30°.In our study, we used Lewinnek's method [14] which was found to be consistent with CT scans values of measured anteversion angles.…”
Section: Discussionmentioning
confidence: 99%
“…However, there still exists a dearth of literature regarding the effects of acetabular component positioning on hip functional outcome scores and till date patient satisfaction as a primary outcome in relation to acetabular version has not been done. Reikeras et al [12] concluded that cross-table radiography provides acceptable information for clinical use. Reikeras et al [13] studied that the range of acetabular component anteversion actually achieved by the use of a cup positioner by the freehand technique in many cases was not within the intended range of 10 to 30°.In our study, we used Lewinnek's method [14] which was found to be consistent with CT scans values of measured anteversion angles.…”
Section: Discussionmentioning
confidence: 99%
“…whereas the mean angle on CT scan was 28.64 0 (Range 11.10-51.10 0 ) with 17(30.90 %) patients were found in Lewinnek safe zone. Reikeras et al [18] concluded that cross-table radiography provides acceptable information for clinical use. Reikeras et al [19] studied that the range of acetabular component anteversion actually achieved by the use of a cup positioner by the freehand technique in many cases was not within the intended range of 10 to 30°.…”
Section: Discussionmentioning
confidence: 99%
“…The mean anteversion angle was 22.41 0 on cross-table lateral radiographs whereas the mean angle of 28.64 0 was reported on CT scan. Reikeras et al [18] postulated that cross table radiography provides acceptable information for clinical use but has limited use for precise analysis of the acetabular cup version. McArthur et al [23] demonstrated properly positioned, cross-table lateral radiograph-derived measurements are similarly accurate as CT measurements.…”
Section: Discussionmentioning
confidence: 99%